HUBUNGAN KEBUTUHAN AFILIASI ANAK DENGAN KEPERCAYAAN DIRI ANAK TK DI DESA JAKE KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Patma, Mitra; Chairilsyah, Daviq; Sari, Enda Puspita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was background by the low level of self-confidence of Kindergarten Jake Village Kuantan Tengah District Kuantan Singingi Regency that was related to the needs of child affiliation. This study aims to determine the relationship between the affiliate needs of children and the confidence of kindergarten children in Jake Village, Central Kuantan District, Kantan Singingi Regency. The type of this research is correlation with quantitative methods. Data collection techniques used are observation. The sampling technique used in this study was simple random sampling. The population was 112 children. Based on the results of calculations using the Taro Yamane formula, the sample size determined in this study was 53 children. The data analysis technique uses a correlation test from the Pearson product moment with the IBM SPSS program. Based on the results of hypothesis testing obtained there is a positive and significant relationship between the affiliate needs of children with children's confidence in Kindergarten Jake Village Kuantan Tengah District Kuantan Singingi Regency. This can be seen from the value of the correlation coefficient of 0.517 which is in the range of 0.40 - 0.599 with the medium category. This means that there is a moderate relationship between the need for affiliation and self-confidenceKeywords: Affiliate Needs, Confidence